COMMON PECULIARITIES OF UZBEK AND ENGLISH FAIRY – TALES - Bakhtiyorova, M.B.; Djumabaeva, J.Sh. (FAN va JAMIYAT, 2018)
The article deals with the analysis of the toponyms in Uzbek and Englisn fairy-tales. The comparative analysis gives an opportunity to distinguish lingua culturological peculiarities of two nations. There has been done toponymic system and toponymic units were investigated on the basis of lexico-semantic analysis.